POLYPHENOLS AND FLAVONOIDS OF TWELVE INDIAN MEDICINAL PLANTS - CHANDA, SUMITRA; BHAYANI , DILIP; DESAI, DISHANT (The Bioscan, 2013)
In the present work, twelve Indian medicinal plants (Averrhoa carambola L., Buchanania lanzan Spr., Calophyllum inophyllum L., Celastrus paniculatus Willd., Clerodendron multiflorum L., Luffa acutangula (L.) Roxb., Morinda citrifolia L., Ocimum gratissimum L., Peltophorum ferrugineum (Decne.), Phyllanthus fraternus Webster Syn., Triumfetta rotundifolia Lam. and Ziziphus nummularia (Burm. F.) were evaluated for their total phenol and flavonoid content. The plant material was extracted individually in different solvents by cold percolation method. Total phenol and flavonoid content was measured by using Folin-Ciocalteu’s reagent method and aluminum chloride colorimeter method respectively. Amongst the twelve plants screened, methanolic extract of P. ferrugineum had highest total phenol and flavonoid content. These results suggest that the methanolic extract of P. ferrugineum can be considered as a medicinal source for the treatment and prevention of many free radical related diseases.